Women business owners' adoption of information and communication technology. Issue 4 (14th November 2016) - Sharafizad, Jalleh
Abstract : Purpose: This study aims to investigate the uptake and usage patterns of information and communication technologies (ICTs) by women small business owners (SBOs). Design/methodology/approach: Semi-structured interviews were conducted with 25 women SBOs who were recruited through purposeful sampling methods. Interview data on communication technologies participants used were broken down into six main categories: internet search, internet advertising, online transactions, telephone, email and fax. Participants were also asked questions regarding proximity between them and different business contacts, and whether technology influenced how they communicated with these individuals. Findings: All participants had moved up from having a basic website to transacting goods and services online. ICTs were used to acquire tangible and intangible resources as well as for informal learning. Geographical distance between SBOs and individuals within their business and convenience of ICT failed to affect participants' preference for face-to-face communication with key business contacts. Research limitations/implications: This study has limitations that tend to be commonly found in exploratory studies, such as a small sample size. However, the findings lay the groundwork for future quantitative studies that examine the potential influence of other factors, such as gender and culture, on adoption of ICT by SBOs. Originality/value: This study responds to a call for research that develops a more nuanced understanding of how women SBOs use ICTs in their business. The findings can be used by policymakers and development agencies in their teaching and training interventions.